Prevalence of Vaginal Candidiasis among Diabetic and Non-Diabetic Pregnant Women in Three Hospitals in Tripoli -Libya - Abourghiba, Taher Y.; Alghadem, Zynab A. (The Libyan Journal of Science, 2020)
The current study was conducted to detect vaginal infections of Candida among diabetic and non-diabetic pregnant women. It was performed on 140 pregnant women who were admitted to three hospitals in Tripoli, Libya from July 2017 to July 2018. Specimens were collected with sterile cotton swabs. Samples were cultured on Sabouraud dextrose agar(SAB). Specimens of fungal growth were examined microscopically for identification of Candida species The results of investigations showed that pregnant women in the age range of 18-29 had higher percentage of Candida infections in comparison with other age groups. Three species of Candida were isolated and identified as Candida albicans, Candida glabrata and Candida tropicalis. There were no significant differences of vaginal infections among pregnant women who have different educational levels.